2003
DOI: 10.1634/theoncologist.8-1-35
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel, Cisplatin, 5-Fluorouracil (TPF)-Based Induction Chemotherapy for Head and Neck Cancer and the Case for Sequential, Combined-Modality Treatment

Abstract: Since the publication of the Veterans Affairs study in the early 1990s, much has been learned regarding the role of chemotherapy, radiation therapy, and more importantly, the role of combined-modality treatment with chemoradiation in the therapy of locally advanced head and neck cancer. There continues to be widespread variation and controversy in the timing, schedule, and intensity of chemotherapy and chemoradiation. Herein, we present the various approaches currently used in the year 2003 with a specific emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 45 publications
(72 reference statements)
0
28
0
2
Order By: Relevance
“…These trials and the several that followed [13][14][15][16] demonstrated the possibility to achieve similar survival rates both using CT-RT or radical surgery, and certainly changed the standard of care in advanced-stage larynx cancer; these emerging data have not been accepted by everyone and most criticism arose, especially on the enrolling criteria of these studies and the possible bias of patients with an earlier stage disease in the experimental arm of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…These trials and the several that followed [13][14][15][16] demonstrated the possibility to achieve similar survival rates both using CT-RT or radical surgery, and certainly changed the standard of care in advanced-stage larynx cancer; these emerging data have not been accepted by everyone and most criticism arose, especially on the enrolling criteria of these studies and the possible bias of patients with an earlier stage disease in the experimental arm of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…4 The taxanes also have been proven to have a significant single-agent activity in SCC of the head and neck. 21 Many regimens have been developed to try to take advantage of the activity of paclitaxel and docetaxel. In a phase III trial performed for a European Organisation for Research and Treatment of Cancer (EORTC) head and neck cancer group, 177 patients with non-resectable locally advanced SCC of the head and neck were treated with docetaxel, cisplatin, 5-FU and leucovorin and they were then compared with the 5-FU regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the local radiotherapy after docetaxel and cisplatin neoadjuvant chemotherapy had an organ preserving effect and the regimen does not increase locoregional failure compared with other reports, including the docetaxel, cisplatin, 5-FU and leucovorin combination chemotherapy. 7,12,21 The effects of treatment on functional abilities such as speech and eating are additional factors to consider for patients with head and neck cancer. Recent attempts to improve the major endpoints of treatment have focused on the use of radiotherapy with concomitant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs essais de ce type ont été réalisés [13,14,24,38] associant en chimiothérapie d'induction 2 à 6 cycles de paclitaxel-carboplatine ± 5Fu, suivie d'une radiochimiothérapie comprenant selon les cas, paclitaxel ± cisplatine ou hydroxyurée-5Fu, la radiothérapie étant classique ou hyperfractionnée (Tableau 2). Tous ces essais indiquent une survie à 3 ans entre 60 et 80 % ce qui est un résultat très encourageant.…”
Section: Stratégie Pour Le Futurunclassified